Non-commutative quantum mechanics : properties of piecewise constant potentials in two dimensions - Thom, Jacobus D. (Jacobus Daniel) (Stellenbosch : University of Stellenbosch, 2010)
Thesis (PhD (Physics))--University of Stellenbosch, 2010.